Mistrzyni. Wspomnienie o Pani Profesor Mirosławie Chamcównie – niezwykłej osobie wywierającej wpływ na uczniów - Ładyżyński, Andrzej (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The heroine of this article, professor Mirosława Chamcówna belonged to the representatives of the Poles born in the Second Republic of Poland. She was highly educated and from the early years of her childhood she was actively engaged in the social and national life. She created the works that brought a significantcontribution into the development of an academic reflection about the fundamental activity dedicated to the National Education Commission in Poland. The students will remember her mainly as a person of a great heart and character.
Keywords: master; Mirosława Chamcówna; personal mode; university teacher